Localization of a spin-orbit-coupled Bose-Einstein condensate in a bichromatic optical lattice - Cheng, Yongshan; Tang, Gaohui; Adhikari, S. K. [UNESP] (American Physical Society (APS), 2014)
We study the localization of a noninteracting and weakly interacting Bose-Einstein condensate (BEC) with spin-orbit coupling loaded in a quasiperiodic bichromatic optical lattice potential using the numerical solution and variational approximation of a binary mean-field Gross-Pitaevskii equation with two pseudospin components. We confirm the existence of the stationary localized states in the presence of the spin-orbit and Rabi couplings for an equal distribution of atoms in the two components. We find that the interaction between the spin-orbit and Rabi couplings favors the localization or delocalization of the BEC depending on the phase difference between the components. We also studied the oscillation dynamics of the localized states for an initial population imbalance between the two components. © 2014 American Physical Society.